2022
DOI: 10.4103/ipj.ipj_127_21
|View full text |Cite
|
Sign up to set email alerts
|

Happiness and its determinants among nursing students

Abstract: Background: Being happy in life is very essential to be healthy, which is important for nursing students to grow and adapt well in their professional life. Aim: The aim of this study is to assess the level of happiness and identify the determinants of happiness among nursing students. Materials and Methods: Three hundred and forty-two undergraduate nursing students College of Nursing, All India Institutes of Medicals Sciences, New Delhi, Indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Their level of satisfaction has a direct impact on how these skills develop. According to Jun and Jo, happiness is essential for the education and development of nursing students as potential nurses [4] .…”
Section: Introductionmentioning
confidence: 99%
“…Their level of satisfaction has a direct impact on how these skills develop. According to Jun and Jo, happiness is essential for the education and development of nursing students as potential nurses [4] .…”
Section: Introductionmentioning
confidence: 99%
“…Happiness is a multidimensional structure that consists of emotional and cognitive elements (Kumar et al 2022). One of these dimensions is the locus of control (LOC).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the plethora of theories on its components (e.g., Kahneman, 1999;Seligman, 2002), happiness is a central topic in public health, research, and applications (e.g., Chrostek, 2016;Pretty & Barton, 2020). As a result, the importance of measuring happiness in various contexts (e.g., De Giorgio et al, 2023;Kumar et al, 2022) has triggered a theoretical and methodological discussion, yielding an astounding plethora of practical tools and approaches throughout time (e.g., Helliwell & Aknin, 2018). The corporate world, institutions, and education have all recently become much more interested in the topic of happiness, which has resulted in awards and certifications (e.g., Great Places to work®, The Awards of Happiness®; Lee & Yoon, Happiness, or the degree to which a person evaluates his\her life positively and favorably (Hart et al, 2018), is a widely and commonly used word, and -as an emotion-it has been identified by numerous authors as one of the basic humans affects (Helliwell & Aknin, 2018;Jebb et al, 2020).…”
mentioning
confidence: 99%